2022
DOI: 10.3390/molecules27196352
|View full text |Cite
|
Sign up to set email alerts
|

Production of Siamenoside I and Mogroside IV from Siraitia grosvenorii Using Immobilized β-Glucosidase

Abstract: Siraitia grosvenorii is a type of fruit used in traditional Chinese medicine. Previous studies have shown that the conversion of saponins was often carried out by chemical hydrolysis, which can be problematic because of the environmental hazards it may cause and the low yield it produces. Therefore, the purpose of this study is to establish a continuous bioreactor with immobilized enzymes to produce siamenoside I and mogroside IV. The results show that the immobilization process of β-glucosidase exhibited the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…S125, were selected to produce corresponding mogrosides. Previous studies have shown high levels of β-glucosidase activities, meaning excellent bioconversion ability for mogrosides (Chen et al 2022 ), as this glycosidase is usually responsible for hydrolyzing the glycosidic bonds of mogrosides. Thus, β-glucosidase activities were selected as a parameter to optimize cultural conditions.…”
Section: Resultsmentioning
confidence: 99%
“…S125, were selected to produce corresponding mogrosides. Previous studies have shown high levels of β-glucosidase activities, meaning excellent bioconversion ability for mogrosides (Chen et al 2022 ), as this glycosidase is usually responsible for hydrolyzing the glycosidic bonds of mogrosides. Thus, β-glucosidase activities were selected as a parameter to optimize cultural conditions.…”
Section: Resultsmentioning
confidence: 99%
“…S.125 were selected to produce corresponding mogrosides. Previous studies have shown high level of β-glucosidase activities meaning excellent ability for bioconversion of mogrosides (Chen et al, 2022), as this glycosidase is usually responsible for hydrolyzing glycosidic bond of mogrosides. Thus, β-glucosidase activities were selected as a parameter to optimize cultural conditions.…”
Section: Phylogenetic Analysis Of Endophytic Fungi With Capacity Of M...mentioning
confidence: 99%